DETERMINATION OF SENSITIZATION TO POLLEN AND FUNGAL ALLERGEN EXTRACTS IN CHILDREN WITH ALLERGIC PATHOLOGY BY IMMUNOCAP METHOD - Panahova, T.T. (World of Medicine and Biology, 2025)
The purpose of the study was to investigate the sensitization of children with allergic pathology to weed pollen and tree pollen, as well as fungal allergens. 220 children with various allergic diseases in the age range from 1 to 17 years were examined. Allergological examination included determination of specific IgE-antibodies in blood serum by ImmunoCAP method (pollen, fungal). Relatively high level of sensitization was noted for cypress evergreen pollen allergen (t23), sIgE level was 2.232±1.515 kU/l (2nd class). Relatively high level of fungal allergens was observed for Alternaria alternata allergen (m6), sIgE level was 2.358±1.215 kU/l (pF=0.912; pU=0.067) (2nd class). Among pollen allergens, sensitization to lanceolate plantain, evergreen cypress and European olive was the most frequent. Hypersensitization to antigens of Alternaria alternata fungus was proved by the conducted studies.
Keywords: sensitization; pollen allergens; fungal allergens; children; allergic pathology; ImmunoCAP method